Constitutional supremacy, rule of law and the supreme policing authority of judiciary: emergence of the doctrine of constitutional oath - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha (2021)
This paper discusses on the constitutional oath of judges although it is true thatoaths as the ritual has been the practice in almost all civilisations across the world since time immemorial, and this tradition continues to these days